Feminist epistemology and philosophy of science power in knowledge - Grasswick, Heidi E.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
This collection brings together exciting new works that address today?s key challenges for a feminist power-sensitive approach to knowledge and scientific practice. Taking up such issues as the role of contextualism in epistemology, democracy and dissent in knowledge practices, and epistemic agency under conditions of oppression, the essays build upon well-established work in feminist epistemology and philosophy of science such as standpoint theory and contextual empiricism, offering new interpretations and applications. Many contributions capture the current engagement of feminist epistemologists with the insights and programs of nonfeminist epistemologists, while others focus on the intersections between feminist epistemology and other fields of feminist inquiry such as feminist ethics and metaphysics. An important resource both for students and scholars of feminist epistemology and philosophy of science, with sections of interest to social epistemologists and philosophers of science more generally, this collection represents the broad array of the feminist epistemological work now being done, and the many ways in which feminists incorporate power dynamics into their analyses. It clearly represents both the breadth and the depth of this now well-developed area of feminist scholarship.
Introduction: Feminist Epistemology and Philosophy of Science in the Twenty-first Century; Heidi E. Grasswick.- I Intersections: Feminism, Epistemology, and Science Studies.- 1. The Marginalization of Feminist Epistemology and What That Reveals About Epistemology Proper; Phyllis Rooney.- 2. Contextualism in Feminist Epistemology and Philosophy of Science; Kristina Rolin.- 3. Altogether Now: A Virtue-theoretic Approach to Pluralism in Feminist Epistemology; Nancy Daukas.- 4. The Implications of the New Materialisms for Feminist Epistemology; Samantha Frost.- 5. Interrogating the Modernity vs. Tradition Contrast: Whose Science and Technology for Whose Social Progress; Sandra Harding.- II Democracy and Diversity in Knowledge Practices.- 6. Is Millian Democratic Science the Right Model for Feminist Science?; Kristen Intemann.- 7. What's in it for me? The Benefits of Diversity in Scientific Communities; Carla Fehr.- 8. What Knowers Know Well: Women, Work and the Academy; Alison Wylie.- III Contexts of Oppression: Accountability in Knowing.- 9. More than Skin Deep: Situated Communities and the Case of Agent Orange in the Aluoi Valley, Viet Nam; Nancy McHugh.- 10. They Treated Him Well: Fact, Fiction, and the Politics of Knowledge; Lorraine Code.- 11. Wrongful Requests and Strategic Refusals to Understand; Gaile Pohlhaus, Jr.- 12. Liberatory Epistemology and Sharing Knowledge: Querying the Norms; Heidi E. Grasswick.- Index.
Electronic reproduction.
Keywords: Feminist theory; Knowledge, Theory of; Electronic books